Modification, by aspirin and indomethacin, of the haemodynamic and prostaglandin releasing effects of E. coli endotoxin in the dog. - Fletcher, J R (1977)
1 Dogs treated with aspirin (10 mg/kg) or indomethacin (1.5 mg/kg) 45 min before, and 3 h after, an LD50 dose (1 mg/kg) of E. coli endotoxin were alive 72 h later. 2 Although all dogs in both treated groups survived, only those treated with indomethacin were protected against the fall in blood pressure 1-2 min following endotoxin. 3 Endotoxin increased the level of prostaglandin F2alpha in both the mixed venous and arterial blood. No increase was observed in the aspirin and indomethacin-treated groups. 4 Aspirin and indomethacin treatment did not modify thrombocytopaenia or blood coagulation parameters following endotoxin.